Pemberdayaan Ekonomi Masyarakat Pesisir melalui Pengolahan Kelapa Terpadu di Pulau Lombok - Muhamad Bai'ul Hak; Moh. Huzaini; Ali Akbar Hidayat; Muhammad Fadlli; Nuryanti; Ade Cahyani Fitri; Adi Septiawan (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
The empowerment of coastal communities through integrated coconut processing aims to enhance participants' knowledge and skills in producing value-added products, particularly cooking oil. This training is designed to enable participants to understand the complete production process, including raw material selection, processing stages, and packaging techniques that meet quality standards. The activity employed a Participatory Action Research (PAR) approach, emphasizing active community involvement throughout all stages: problem and needs identification, participatory action planning, implementation, and collaborative evaluation and reflection. The results showed a significant improvement in participants' understanding and skills, especially in producing hygienic and efficient coconut-based cooking oil and designing attractive packaging that meets market standards.